LOS HONGOS MICORRIZÓGENOS ARBUSCULARES COMO COMPONENTES DE LA BIODIVERSIDAD DEL SUELO EN MÉXICO - Varela, Lucia; Trejo, Dora (Instituto de Ecología, A.C., 2001)
Arbuscular mycorrhizas are one of the most widespread mutualistic symbioses which occur between roots of most herbaceous and tropical trees and a small group of root colonizing fungí, Order Glomales. Thís symbiosis ís characterized by the movement of mineral nutriente acquired by the fungí towards the plant in exchange for providing the fungí with carbón compounds. In México, the taxonomíc diversíty of arbuscular mycorrhizal fungí (AMF) has been poorly studied, since most of studies have been focused to determíne plant responses to mycorrhíza without consídering the origin or identity of the endophyte. In this country 44 species of AMF have been recorded, representing 29% of the woridwide known species. Most of these records come from agricultural systems and oniy seven species come from natural ecosystems. These 44 species have been oniy found in 11 of the 32 States of México. Even though the taxonomíc knowledge and handiing of these fungí ís quite limited, fieid work with plants inoculated in greenhouse has been carríed out in the last years. Nevertheless,intormíUiun is ruíjuifíid rf:g,írding fieid persistencc of tho findophyte ynd its cftcct on soil miorobiotci divorsity. Knowledye of tho composition and diversity of AMF is importan! for proper handhng ot soil plant fungos intoraotion in ordur to achieve sustainable systerns.